Pengaruh Pengungkapan ESG dan Profitabilitas Terhadap Agresivitas Pajak Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Dinata, Ananda Sella; Rizki, Marsi Fella (Gorontalo State University, 2026)
This study aims to analyze the effect of ESG disclosure and profitability on tax aggressiveness, with company size as a moderating variable in energy sector issuers on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. From a population of 91 companies, 13 samples were selected through a purposive sampling method, resulting in 39 observations for analysis using panel data regression and Moderated Regression Analysis (MRA). The study results show that ESG disclosure has a significant negative effect (ẞ = -0.354013, p = 0.0388), while profitability has a significant positive effect (p = 0.0366) on tax aggressiveness. Company size is proven to significantly weaken the impact of profitability on tax aggressiveness (p = 0.0437), but no moderating effect is found on the ESG variable. With an Adjusted R-Square value of 0.571371, this model is able to explain 57.13% of the variation in tax aggressiveness. These findings emphasize the importance of the energy sector in integrating ESG standards and ethical earnings management to mitigate the risk of aggressive tax practices.